Lipoprotein(a) is Markedly More Atherogenic than LDL: An Apolipoprotein B-based Genetic Analysis - Björnson, Elias (J Am Coll Cardiol, 2024)
BACKGROUND AND AIMS: Lipoprotein (a) (Lp(a)) is recognised as a causal factor for coronary heart disease (CHD) but its atherogenicity relative to that of LDL on a per particle basis is indeterminate. OBJECTIVES: We addressed this issue in a genetic analysis based on the fact that Lp(a) and LDL both contain one apolipoprotein B per particle. METHODS: Genome wide association studies using the UK Biobank population identified two clusters of SNPs: one comprising 107 variants linked to Lp(a) mass concentration, the other with 143 variants linked to LDL concentration. In these ‘Lp(a)’ and ‘LDL’ clusters, the relationship of genetically-predicted variation in apoB with CHD risk was assessed. RESULTS: The Mendelian randomisation-derived odds ratio for CHD for a 50 nmol/L higher Lp(a)-apoB was 1.28 [95% confidence interval (CI):1.24-1.33] compared to 1.04 [95%CI:1.03-1.05] for the same increment in LDL-apoB. Likewise, use of polygenic scores to rank subjects according to difference in Lp(a)-apoB vs. difference in LDL-apoB revealed a greater hazard ratio for CHD per 50nmol/l apoB for the ‘Lp(a)’ cluster (1.47 [95%CI:1.36-1.58]) compared to the ‘LDL’ cluster (1.04 [95%CI:1.02-1.05]). From these data, we estimate that the atherogenicity of Lp(a) is around 6-fold [point estimate of 6.6; 95% CI:5.1-8.8] greater than that of LDL on a per particle basis. CONCLUSIONS: We conclude that the atherogenicity of Lp(a) (coronary heart disease risk quotient per unit increase in particle number) is substantially greater than that of LDL. Therefore, Lp(a) represents a key target for drug-based intervention in a significant proportion of the at-risk population.